Shaped adsorbent and water purification filter cartridge

CN122995904APending Publication Date: 2026-10-27LIXIL CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202480090083.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-04-03
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

用于解决技术问题的技术方案

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122995904A_ABST
    Figure CN122995904A_ABST
Patent Text Reader

Abstract

The present invention provides a molded adsorbent capable of improving a chloroform removal performance. A molded adsorbent (1) contains activated carbon (3) and a fibrous binder (7), wherein the central particle diameter D50 of the activated carbon (3) is 16 μm or more and less than 27 μm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to shaped adsorbents and water purification filter cartridges. Background Technology

[0002] Patent Document 1 discloses a water treatment filter. The water treatment filter of Patent Document 1 includes a cylindrical filter comprising granular activated carbon with a central particle size of 30 μm or more and 80 μm or less, and fibrillated fibrous binder. Existing technical documents Patent documents

[0003] Patent Document 1: WO2014 / 061740 Summary of the Invention The technical problem that the invention aims to solve

[0004] The chloroform removal capability of the water treatment filter in Patent Document 1 may not be sufficient. The purpose of this disclosure is to provide a shaped adsorbent that can improve chloroform removal performance. Technical solutions for solving technical problems

[0005] The shaped adsorbent disclosed herein contains activated carbon and a fibrous binder, wherein the central particle size D50 of the activated carbon is greater than 16 μm and less than 27 μm. Attached Figure Description

[0006] Figure 1 This is an illustrative diagram schematically representing the structure of a shaped adsorbent. Figure 2 This is a front view of an example of a water filter cartridge with a shaped adsorbent. Figure 3 yes Figure 2 A cross-sectional view of a water purification filter cartridge. Figure 4 It is a frequency distribution curve plotted for fibrous adhesives, with the horizontal axis set to particle size and the vertical axis set to frequency. Figure 5 It is a cumulative distribution curve plotted for fibrous adhesives, with the horizontal axis set to particle size and the vertical axis set to cumulative volume. Detailed Implementation

[0007] First, embodiments of this disclosure are listed for description. Regarding the following multiple embodiments, any combination of embodiments without contradiction is also included in the specific embodiments of this invention. [1] The shaped adsorbent disclosed herein contains activated carbon and fibrous binder, wherein the central particle size D50 of the activated carbon is greater than 16 μm and less than 27 μm. [2] According to the shaped adsorbent described in [1] above, when the fibrous adhesive is measured using a laser diffraction / scattering particle size distribution measuring device, the measured value obtained as the central particle size D50 is 50 μm or more and 140 μm or less. [3] The shaped adsorbent according to [1] or [2] above further contains one or more lead removal materials selected from the group consisting of zeolite, titanium silicate, sodium titanate, aluminosilicate and titanium oxide, wherein the central particle size D50 of the lead removal material is 25 μm or more and 40 μm or less. [4] The shaped adsorbent according to any one of [1] to [3] above, wherein when the shaped adsorbent is set to 100% by mass, the content of the fibrous adhesive is 4% by mass or more and 12% by mass or less. [5] The water purification filter element disclosed herein comprises the shaped adsorbent described in any one of [1] to [4] above.

[0008] The embodiments of this disclosure will be described with reference to the accompanying drawings. It should be noted that in this specification, the terms "above" and "below" are used to describe numerical ranges, and unless otherwise specified, they include both the lower limit and the upper limit. For example, the statement "10 or more and 20 or less" includes both "10" as the lower limit and "20" as the upper limit. Furthermore, in this specification, the upper and lower limits of each numerical range can be arbitrarily combined.

[0009] like Figure 1 As shown, the shaped adsorbent 1 of this embodiment contains activated carbon 3 and fibrous binder 7. The shaped adsorbent 1 may also contain one or more lead removal materials 5 selected from the group consisting of zeolite, titanium silicate, sodium titanate, aluminosilicate, and titanium oxide. Figure 1 This is an illustrative diagram schematically representing the structure of the formed adsorbent 1. The size, shape, and amount of each component are not limited thereto. Figure 1 The arrow indicates the direction of water flow purified by the shaped adsorbent 1.

[0010] Activated carbon 3 can be obtained from any starting material. Specific examples of activated carbon 3 include activated carbon obtained by carbonizing and activating one or more of the following materials at high temperature: coconut shell, rice husk, coal, and phenolic resin. The form of activated carbon 3 is not particularly limited. Activated carbon 3 may be, for example, in granular form.

[0011] In the past, shaped adsorbents used activated carbon with a central particle size (D50) of approximately 65 μm to suppress pressure loss, ensure turbidity filtration performance, and maintain a balance in the removal of free residual chlorine. The inventors of this application developed a method to improve the chloroform removal capacity specified in JIS S3201:2019, based on the assumption that finer particle size of activated carbon is effective. However, while improving chloroform removal capacity by making the activated carbon finer than before, it is difficult to ensure the initial flow rate required for a shaped adsorbent. Through repeated and in-depth research, the inventors of this application have developed a new technique that combines activated carbon 3 with a central particle size (D50) within the specified range with a fibrous binder 7, in accordance with this disclosure.

[0012] From the viewpoint of ensuring initial flow rate, the central particle size D50 of activated carbon 3 is 16 μm or more, preferably 19 μm or more, and more preferably 20 μm or more. From the viewpoint of improving chloroform removal capacity, the central particle size D50 of activated carbon 3 is less than 27 μm, preferably 26 μm or less, and more preferably 25 μm or less. From these viewpoints, the central particle size D50 of activated carbon 3 is 16 μm or more and less than 27 μm, preferably 19 μm or more and 26 μm or less, and more preferably 20 μm or more and 25 μm or less.

[0013] From the viewpoint of improving chloroform removal capacity, the content of activated carbon 3 with a particle size of 10 μm or less is preferably 1% by volume or more, more preferably 3% by volume or more, even more preferably 5% by volume or more, and can be 7% by volume or more, or 8% by volume or more. From the viewpoint of ensuring initial flow rate, the content of activated carbon 3 with a particle size of 10 μm or less is preferably 15% by volume or less, more preferably 10% by volume or less, and even more preferably 8% by volume or less. From these viewpoints, the content of activated carbon 3 with a particle size of 10 μm or less is preferably 1% by volume or more and 15% by volume or less, more preferably 3% by volume or more and 10% by volume or less, and even more preferably 5% by volume or more and 8% by volume or less. The content of activated carbon 3 with a particle size of 10 μm or less refers to the volume percentage of activated carbon 3 with a particle size of 10 μm or less contained in 100% by volume of the total amount of activated carbon 3. The particle size of activated carbon 3 with a particle size of 10 μm or less is greater than 0 μm.

[0014] The central particle size D50 of activated carbon 3 and the content of activated carbon 3 with a particle size of less than 10 μm can be determined by a laser diffraction / scattering particle size distribution measuring device.

[0015] The central particle size D50 and particle size distribution of activated carbon 3 can be controlled, for example, by appropriately selecting the particle size of the activated carbon used as raw material. When activated carbon 3 is a mixture of activated carbons with different particle sizes, the mixing amount of activated carbons of each particle size can be adjusted for control.

[0016] The content of activated carbon 3 is not particularly limited. When the shaped adsorbent 1 is set to 100% by mass, the content of activated carbon 3 is preferably 64% by mass or more and 96% by mass or less, more preferably 75% by mass or more and 94% by mass or less, and even more preferably 80% by mass or more and 92% by mass or less.

[0017] The fibrous adhesive 7 is not particularly limited as long as it does not affect the desired effect. The fibrous adhesive 7 can be synthetic or natural fibers. For example, the fibrous adhesive 7 is selected from one or more fibers chosen from the group consisting of acrylic fibers, polyethylene fibers, polypropylene fibers, polyacrylonitrile fibers, cellulose fibers, polyamide fibers, and aromatic polyamide fibers. Acrylic fibers are preferred. From the viewpoint of maintaining the shape of the formed adsorbent 1, it is preferable that the fibrous adhesive 7 is fibrillated.

[0018] It should be noted that, as is known in the present disclosure, the fibrous adhesives 7, 7A, and 7B can also be appropriately evaluated through particle size distribution measurement, just like the particle size distribution of activated carbon 3. Therefore, the fibrous adhesives 7, 7A, and 7B of the present disclosure are defined by the measured values ​​obtained using a laser diffraction / scattering particle size distribution measuring device.

[0019] When measuring the fibrous adhesive 7 using a laser diffraction / scattering particle size distribution measuring device, the measured value obtained as the central particle size D50 is preferably 50 μm or more and 140 μm or less, more preferably 70 μm or more and 130 μm or less, and even more preferably 90 μm or more and 120 μm or less.

[0020] From the viewpoint of ensuring the shape retention of the formed adsorbent 1 and the filling amount of activated carbon 3, the fibrous binder 7 is preferably a mixture of a first fibrous binder 7A and a second fibrous binder 7B having a different particle size distribution than the first fibrous binder 7A. The first fibrous binder 7A and the second fibrous binder 7B can be of the same type of fiber or different types of fiber, provided they have different particle size distributions. The first fibrous binder 7A and the second fibrous binder 7B are preferably of the same type of fiber, and more preferably both are acrylic fibers. Such a second fibrous binder 7B can be obtained, for example, by subjecting the first fibrous binder 7A to a particle size reduction process. The particle size reduction process includes, for example, pulverization or grading.

[0021] When measuring the first fibrous adhesive 7A using a laser diffraction / scattering particle size distribution measuring device, the measured value as the central particle size D50 is preferably 60 μm or more and 300 μm or less, more preferably 80 μm or more and 200 μm or less, and even more preferably 100 μm or more and 160 μm or less. When measuring the second fibrous adhesive 7B using a laser diffraction / scattering particle size distribution measuring device, the measured value as the central particle size D50 is preferably 14 μm or more and 60 μm or less, more preferably 18 μm or more and 40 μm or less, and even more preferably 20 μm or more and 30 μm or less.

[0022] The ratio (mass ratio) of the first fibrous adhesive 7A to the second fibrous adhesive 7B is not particularly limited. The mass ratio of the first fibrous adhesive 7A to the second fibrous adhesive 7B is preferably 5:5 to 9.9:0.1, more preferably 6:4 to 9.5:0.5, and even more preferably 7:3 to 9:1.

[0023] The content of the fibrous adhesive 7 is not particularly limited. When the shaped adsorbent 1 is set to 100% by mass, the content of the fibrous adhesive 7 is preferably 4% by mass or more and 12% by mass or less, more preferably 5% by mass or more and 11% by mass or less, and even more preferably 6% by mass or more and 10% by mass or less.

[0024] The lead removal material 5 is not particularly limited, provided it does not affect the desired effect. The lead removal material 5 may be, for example, one or more selected from the group consisting of zeolite, titanium silicate, sodium titanate, aluminosilicate, and titanium oxide, with zeolite being preferred. The form of the lead removal material 5 is not particularly limited. The lead removal material 5 may be, for example, in particulate form.

[0025] From the viewpoint of ensuring water flow rate by matching the particle size of activated carbon 3, the central particle size D50 of lead removal material 5 is preferably 25 μm or more and 40 μm or less, more preferably 28 μm or more and 37 μm or less, and even more preferably 30 μm or more and 35 μm or less. The central particle size D50 of lead removal material 5 can be measured using a laser diffraction / scattering particle size distribution measuring device.

[0026] The content of lead-removing material 5 is not particularly limited. When the shaped adsorbent 1 is set to 100% by mass, the content of lead-removing material 5 is preferably 2.5% by mass or more and 32% by mass or less, more preferably 3.0% by mass or more and 20% by mass or less, and even more preferably 4.5% by mass or more and 12% by mass or less.

[0027] The pressure loss of the shaped adsorbent 1 is preferably 0.07 MPa or more and 0.15 MPa or less. Such a pressure loss makes the shaped adsorbent 1 practical. Pressure loss refers to the pressure loss when water flows from the outer circumference to the inner circumference at a flow rate of 1.5 L / min in a cartridge filter with an outer diameter of 24.4 mm, an inner diameter of 8.1 mm, and a length of 90.0 mm and a filtration volume of 37.4 mL.

[0028] The density of the formed adsorbent 1 is preferably 0.28 g / cm³. 3 Above and 0.45g / cm 3 The preferred value is 0.35 g / cm³. 3 Above and 0.43 g / cm 3 The following is a further preferred value: 0.38 g / cm³ 3 Above and 0.41 g / cm 3 The density of the shaped adsorbent 1 is defined based on its mass (g) and volume (cm³). 3 The apparent density is calculated from this.

[0029] The water purification filter element 11 of this embodiment includes a shaped adsorbent 1. The shape and structure of the water purification filter element 11 are not particularly limited. Figure 2 and Figure 3 As shown, an example water filter cartridge 11 is cylindrical. This water filter cartridge 11 includes a core 12, a shaped absorbent 1, a non-woven fabric 14, and sealing caps 15 and 16. The core 12 is cylindrical and disposed at the innermost part of the water filter cartridge 11. The core 12 has fine pores that allow water to pass through from the outside to the inside, and a flow path 20 is formed inside. The core 12 can be made of any material. For example, the material of the core 12 is porous ceramic, porous metal filter, or rigid non-woven fabric.

[0030] In one example, the shaped absorbent 1 is cylindrical and disposed on the outer peripheral surface of the core 12. Nonwoven fabric 14 is disposed on the outer peripheral surface of the shaped absorbent 1. The nonwoven fabric 14 may be, for example, a nonwoven fabric specified in JIS L0222. There are no particular limitations on the type of fiber used as the raw material for the nonwoven fabric 14.

[0031] The sealing cap 15 blocks one side of the flow path 20 by covering one end of the shaped adsorbent 1. The sealing cap 16 covers the other end of the shaped adsorbent 1. An outlet 60 is formed in the sealing cap 16 for the discharge of water flowing in the flow path 20.

[0032] There is no particular limitation on the manufacturing method of the water purification filter element 11. The manufacturing method of the water purification filter element 11 may include a mixing process, a suction forming process, a drying process, a surface grinding process, a non-woven fabric winding process, and a sealing process.

[0033] The mixing process involves mixing particulate matter containing at least activated carbon, fibrous binder 7, and water to obtain a slurry. The suction forming process shapes the adsorbent 1. For example, the suction forming process includes: sealing one end of the flow path 20 of the core 12; connecting one end of the flow path 20 of the core 12 to a suction pump via a hose; immersing the core 12 connected to the suction pump in the aforementioned slurry accumulated in a container; and operating the suction pump; water in the slurry permeates through the core 12, and the mixture of particulate matter and binder remains and gradually accumulates on the surface of the core 12. Water in the slurry suctioned by the suction pump is discharged through a drainage path. By operating the suction pump, the shaped adsorbent 1 is formed to a predetermined thickness.

[0034] The drying process dries the shaped adsorbent 1 formed in the suction forming process. The surface grinding process grinds the outer peripheral surface of the shaped adsorbent 1. The nonwoven fabric winding process winds nonwoven fabric 14 around the outer peripheral surface of the shaped adsorbent 1 after grinding in the surface grinding process. The sealing process installs a sealing cap 15 on one end of the shaped adsorbent 1 with nonwoven fabric 14 wound on it, and a sealing cap 16 on the other end.

[0035] As explained above, the shaped adsorbent 1 of this embodiment contains activated carbon 3 and fibrous binder 7, wherein the central particle size D50 of the activated carbon 3 is 16 μm or more and less than 27 μm. The shaped adsorbent 1 of this embodiment can achieve sufficient chloroform removal performance. By using activated carbon 3 and fibrous binder 7 in combination, the shaped adsorbent 1 can appropriately ensure the shape retention and initial flow rate required for the shaped adsorbent 1. Example

[0036] Experimental Examples 2 to 11 are examples, and Experimental Example 1 is a comparative example. In Table 1, "*" indicates a comparative example.

[0037] The formed adsorbents for each experimental example were prepared as described below. First, the experimenter prepared a slurry with a total mass of 100% activated carbon, lead-removing material, and fibrous binder, according to the following mixing ratio. <Slurry mixing ratio> Activated carbon: 80% by mass or more and 92% by mass or less; Lead-free materials: 4.5% by mass or more and 12% by mass or less; Fibrous adhesives: 6% by mass or more and 10% by mass or less.

[0038] Details of each ingredient are shown below. - Activated carbon: Particle-shaped activated carbon having the particle size distribution described in Table 1; - Lead removal materials: zeolite BASF Japan ATS TM MEDIA NSF / ANSI61 D50=29μm; - Fiber adhesive: A mixture of the first and second fiber adhesives in a mass ratio of 87.5:12.5. The measured D50 value is 105.37 μm; First fiber binder: Toyobo Co., Ltd., and Exlan Kogyo Co., Ltd. of Japan, Bi-PUL 50 TWF (acrylonitrile fibrillated fiber). The measured D50 value is 131.5 μm; Second fiber binder: The first fiber binder is pulverized and graded, and the D50 value is adjusted to 25 μm.

[0039] Figure 4 It is a frequency distribution curve plotted for fibrous adhesives, with the horizontal axis set to particle size (μm) and the vertical axis set to frequency (%). Figure 5 This is a cumulative distribution curve plotted for fibrous adhesives, with the horizontal axis set to particle size (μm) and the vertical axis set to cumulative volume (%). The distribution curve for the first fibrous adhesive is shown as "Sample A". The distribution curve for the second fibrous adhesive is shown as "Sample B". The distribution curve for the fibrous adhesive with a measured D50 of 105.37 μm used in each experimental example is shown as "Sample 2". It should be noted that the curves for "Sample 1", "Sample 3", and "Sample 4" are distribution curves for fibrous adhesives with varying mass ratios of the first and second fibrous adhesives, and were not used in this experimental example.

[0040] The details of the particle size distribution measuring apparatus and the measurement conditions are shown below. The particle size distribution was measured using a wet method. The particle size of each substance in the solvent remained unchanged in the dried, formed adsorbate. The particle size distribution of each substance in the solvent reflected the particle size distribution of each substance in the dried, formed adsorbate. The results are recorded in Table 1. Laser diffraction / scattering particle size distribution measurement device: Microtrac MT3300EXII; Distribution: Volume; Solvent: Water; Measurement range: Particle size 0.021 μm to 2000 μm; Number of channels: 132.

[0041] [Table 1]

[0042] Next, the experimenter installed a ceramic core material (outer diameter φ8.1mm, inner diameter φ5.0mm) as the central core on a molding machine, and deposited it in the slurry through suction to form a molded adsorbent. The dimensions of the molded adsorbent were set as outer diameter φ24.4mm, inner diameter φ8.1mm, and length 90mm. The experimenter dried and ground the molded adsorbent, wound it with non-woven fabric, and glued a cap to it to produce a water purification filter cartridge. The density of each molded adsorbent (g / cm³) was determined. 3 The mass (g) of the formed adsorbate was measured and divided by the volume of the formed adsorbate, which was 37.4 cm³. 3 The results were calculated and recorded in Table 1.

[0043] The initial flow rate was evaluated according to JIS S3201 6.1 "Filter Flow Rate Test" as follows. Unused water filter cartridges from each test case were installed on the housing. Raw water was continuously passed through at SV = 2400 / h (1.5 L / min) for 10 minutes. While continuing to pass water, the pressure gauge was adjusted to 0.1 MPa, and the flow rate (LPM, L / min) was measured. The results are recorded in Table 1.

[0044] For Experiments 1 to 11, a linear approximation curve was obtained using the least squares method to determine the relationship between the particle size distribution D50 (μm) of the activated carbon and the initial flow rate (LPM). The obtained linear approximation curve is expressed by the following equation. The coefficient of determination R of the linear approximation curve is... 2 It is 0.86. Initial flow rate (LPM) = 0.0701 × x + 0.377, where x represents the particle size distribution D50 (μm) of the activated carbon.

[0045] The chloroform removal performance was evaluated according to JIS S3201 as follows. Test water with a chloroform concentration of 60 ppb was prepared. The water purification filter cartridges of each test example were installed on the housing, and water was passed through at SV = 2400 / h (1.5 L / min). The cumulative flow rate (L) until the removal rate of the filtered water relative to the raw water reached 80% was measured. Hereinafter, this cumulative flow rate (L) will also be referred to as the chloroform removal performance (L). The results are recorded in Table 1.

[0046] For Experiments 1 to 11, a linear approximation curve was obtained using the least squares method to determine the relationship between the particle size distribution D50 (μm) of activated carbon and its chloroform removal performance (L). The obtained linear approximation curve is expressed by the following formula. The coefficient of determination R of the linear approximation curve is... 2 It is 0.695. Chloroform removal performance (L) = -24.8 × x + 1893, where x represents the particle size distribution D50 (μm) of activated carbon.

[0047] Based on the linear approximation curve representing the relationship between the particle size distribution D50 of the activated carbon and the chloroform removal performance (L), the estimated values ​​of the chloroform removal performance (L) for each experimental example were calculated. The results are recorded in the "Estimated Values ​​of Chloroform Removal Performance (L)" column of Table 1.

[0048] The results of the experiments are as follows. Experiments 2 through 11 all satisfy conditions a, b, and c. In contrast, Experiment 1 does not satisfy condition b. Condition a: Contains activated carbon and fibrous binder. Condition b: The center particle size D50 of the activated carbon is greater than 16μm and less than 27μm. Condition c: Able to form and produce a shaped adsorbent.

[0049] In Experiments 2 through 11, the estimated chloroform removal performance was above 1200 L, and the initial flow rate was above 1.50 LPM. These experiments, while improving chloroform removal capacity, ensured the initial flow rate required for a shaped adsorbent. Explanation of reference numerals in the attached figures

[0050] 1: Formed adsorbent; 3: Activated carbon; 5: Lead removal materials; 7: Fibrous adhesive; 7A: First fibrous adhesive; 7B: Second fibrous adhesive; 11: Water purifier filter cartridge; 12: SMIC; 14: Non-woven fabric; 15: Sealing cap; 16: Sealing cap; 20: Flow path; 60: Discharge outlet.

Claims

1. A shaped adsorbent comprising activated carbon and a fibrous binder, characterized in that, The activated carbon has a center particle size D50 of 16 μm or more and less than 27 μm.

2. The shaped adsorbent according to claim 1, characterized in that, When the fibrous adhesive is measured using a laser diffraction / scattering particle size distribution measuring device, the measured value as the central particle size D50 is 50 μm or more and 140 μm or less.

3. The shaped adsorbent according to claim 1 or 2, characterized in that, It also contains one or more lead removal materials selected from the group consisting of zeolite, titanium silicate, sodium titanate, aluminosilicate, and titanium oxide. The center particle size D50 of the lead removal material is greater than 25 μm and less than 40 μm.

4. The shaped adsorbent according to any one of claims 1 to 3, characterized in that, When the shaped adsorbent is set to 100% by mass, the content of the fibrous adhesive is 4% by mass or more and 12% by mass or less.

5. A water purification filter element, characterized in that, The shaped adsorbent comprises any one of claims 1 to 4.

Citation Information

Patent Citations

  • Water processing filter and manufacturing method therefor

    WO2014061740A1